Establishing a food list for a Total Diet Study: how does food consumption of specific subpopulations need to be considered? - Akhandaf, Y; De Henauw, S; Dofkova, M; Ruprich, J; Papadopoulos, A; Sirot, V; Kennedy, M C; Pinchen, H; Blume, K; Lindtner, O; Brantsaeter, A L; Meltzer, H M; et al. (Food additives & contaminants. Part A, Chemistry, analysis, control, exposure & risk assessment, 2015)
A Total Diet Study (TDS) consists of selecting, collecting and analysing commonly consumed foods to obtain concentration data of different chemical compounds in foods as eaten. A TDS food list summarises the most consumed foods and represents the dietary habits of the general population of the country under study. The work reported here investigated whether TDS food lists that were initially designed for the whole population of the country under study also sufficiently cover the dietary pattern of specific subpopulations that are extra vulnerable for certain contaminants. The work was performed using data of three European countries: the Czech Republic, France and the UK. Each national food consumption database was combined with the corresponding national TDS food list (containing 336, 212 and 119 food items for the Czech Republic, France and the UK, respectively). The data were aggregated on the highest level of hierarchy of FoodEx-1, a pan-European food classification system, including 20 main FoodEx-1 groups. For the group 'milk and dairy products', the coverage of the consumption by the food list was investigated for more refined subgroups. For each food group or subgroup and country, the average percentage of coverage of the diet by the national TDS food list was calculated for different subpopulations, including children versus adults, women versus men, vegetarians versus non-vegetarians, and women of child-bearing age versus older women. The average diet of the different subpopulations was sufficiently covered by the food list of the Czech Republic and France. For the UK the average coverage was low due to a different food-coding approach and because food lists were not derived directly from national food consumption data. At the level of the 20 main food groups, differences between the subpopulations with respect to the average coverage of consumption by the TDS food list were minimal. The differences were more pronounced when looking in detail at the coverage of the dairy consumption. TDS food lists based on the mean consumption of the general population are also applicable to study the chemical exposure of different subpopulations, e.g. children, women of child-bearing age and vegetarians. This lowers the effort when performing a TDS.
Keywords: Spojené království; dítě; France; přijímání potravy; Česká republika; Eating; Aged; stravovací zvyklosti; Age Factors; lidé středního věku; senioři; lidé; Sex Factors; Adult; Czech Republic; Middle Aged; dospělí; Diet; Food; Female; dieta; věkové faktory; Male; ženské pohlaví; sexuální faktory; Child; Humans; mužské pohlaví; Feeding Behavior; United Kingdom; Francie; potraviny